Efficiencies of O-MBR and A/O-MBR for Organic Matter Removal from and Trihalomethane Formation Potential Reduction in Domestic Wastewater - Sornsiri Sriboonnak; Aegkapan Yanun; Phacharapol Induvesa; Chayakorn Pumas; Kritsana Duangjan; Pharkphum Rakruam; Saoharit Nitayavardhana; Prattakorn Sittisom; Aunnop Wongrueng (Membranes, 2022)
Lab-scale anoxic/oxic membrane bioreactor (A/O-MBR) and oxic membrane bioreactor (O-MBR) systems using a submerged polysulfone hollow-fiber membrane module with a pore size of 0.01 μm and a total surface area of 1.50 m2 were used to treat domestic wastewater. The sludge retention time (SRT) of each system was examined by setting the SRT to 10, 20, and infinity (no sludge withdrawal). The results showed that the total nitrogen removal efficiency of the A/O-MBR was more significant than that of the O-MBR at a SRT of infinity, with figures of 72.3% and 33.1% being found, respectively. The COD removal efficiencies of the A/O-MBR system with a SRT of 10 days, 20 days, and infinity were 82.4%, 84.3%, and 91.5%, respectively. The COD removal efficiencies of the O-MBR system with a SRT of 10 days, 20 days, and infinity were 79.3%, 81.5%, and 89.8%, respectively. An increase in the SRT resulted in an increase in the COD removal efficiency. The FEEM peak of the influent tended to decrease after an increase in the SRT for both systems (A/O-MBR and O-MBR). For the A/O-MBR system, the trihalomethane formation potential (THMFP) was significantly reduced by 88.91% (at a SRT of infinity). The THMFP declined significantly by 85.39% for the O-MBR system at a SRT of infinity. The A/O-MBR system showed a slightly higher efficiency than the O-MBR system in terms of the COD removal and the THMFP reduction. These results indicated that the MBR process, and the A/O-MBR system, in particular, could be used as an effective wastewater treatment process for many developing countries that are troubled by the emerging contamination of water and wastewater.